Timeliness of routine vaccination among children and determinants associated with age-appropriate vaccination in Mongolia. Issue 9 (September 2020) - Rauniyar, Santosh Kumar; Munkhbat, Enkhtuya; Ueda, Peter; Yoneoka, Daisuke; Shibuya, Kenji; Nomura, Shuhei
Abstract: Introduction: Routine vaccination at the recommended age is crucial to minimize the risk of acquiring vaccine preventable diseases. This study aimed to assess the proportion of children receiving routine immunization at the recommended age and determinants of timely (age-appropriate) vaccination in Mongolia. Material and method: A total of 879 eligible children aged 12–23 months were included in this study. We investigated age-appropriate administration of Bacillus Calmette-Guerin vaccine (BCG); hepatitis B vaccine (Hep B); oral polio vaccine (OPV); pentavalent vaccine; and measles, mumps, and rubella vaccine (MMR) using Kaplan-Meier method. Multilevel logistic regression with random intercept at cluster level was used to assess the determinants of age-appropriate vaccination. Results: Overall, the crude vaccination coverage for routine vaccinations were above 90% for all vaccines except MMR1 which was 86.0% (95% CI, 83.6–88.2). While the first dose of almost all the vaccines given at birth; BCG, Hep B, and OPV0, were administered in a timely manner, a substantial proportion of second and third doses of these vaccines were not given in a timely manner with age-appropriate vaccination coverage ranging from 35.9% (32.8–39.1%) for MMR1 to 67.7% (64.5–70.7%) for OPV1 respectively. Factors associated with age-appropriate administration of the investigated vaccines included socio-economic status of household, religion of household heads, area of residence, owning mobile phone, and season of childbirth. For instance, children belonging to households from richer wealth quintile had higher possibilities of getting age-appropriate OPV1-OPV3, PE1-PE3 and MMR1 vaccines compared to those from the poorest household wealth quintile. Conclusion: Our findings suggest that the commonly used indicator 'crude vaccination coverage' could be supplemented by 'age-appropriate vaccination' to help to identify gaps in timely vaccinations and stimulate interventions in Mongolia. Factors such as household wealth quintile, place of residence and religion associated with timely vaccination in our study could be considered to promote effective intervention aiming to improve adequate vaccination coverage. Abstract : Vaccines; Delay, Pediatrics; Timeliness, Vaccine coverage, Vaccination, Immunization.